PENGEMBANGAN ENSIKLOPEDIA MINI MATEMATIKA BERBANTUAN APLIKASI CANVA PADA MATERI BANGUN RUANG KELAS 5 SD - I Gede Nastra, I Gede Nastra; I Komang Wahyu Wiguna; I Gede Arya Wiradyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study was motivated by the lack of concrete visualizations in 3D geometry instruction and the limited availability of flexible digital resources. This development research aims to design, validate, and evaluate the practicality of a learning medium a Mathematics Mini-Encyclopedia created using Canva focused on 3D shapes for fifth-grade elementary school students. Employing the Research and Development (R&D) method with the ADDIE model, the study was conducted in the Gugus III Sukasada , involving instrument, subject matter, media, and language experts, as well as fifth-grade teachers and students as trial participants. Data collection techniques included observation, interviews, documentation, and questionnaires. Instrument validity was analyzed using the Gregory matrix formula, product validity was assessed via the Aiken’s V formula, and practicality was measured based on response percentages. The results indicate that the mini-encyclopedia’s design integrates microlearning principles with a QR Code-based print-digital approach. Experts categorized the medium as highly valid, and both teachers and students rated it as highly practical during small-group trials. Consequently, this Mathematics Mini-Encyclopedia is a suitable for enhancing the quality of geometry instruction in elementary schools.